Mapeamento das revistas do portal de periódicos da Universidade Federal do Pará: uma abordagem sobre a importância da elaboração de políticas e estratégias de preservação digital - BARROS, Diego Bil Silva (Universidade Estadual de Londrina, 2019)
Introduction: Addresses the importance of developing policies and strategies for digital preservation, based on an evaluation carried out in the Journal Portal of the Federal University of Pará. Currently, this journal portal is composed by eleven journals, namely: Complexitas, Interdisciplinary Margins, Arterials, Journal Amazon, Agroecosystems Magazine, MOARA, Amazon, New NAEA Notebooks, Hendu, Brazilian Journal of Analysis of Behavior, View the Education Magazine. Objective: It proposes to map the magazines of the Portal of Periodicals of UFPA, identifying strategies and preservation policies, as well as generate practical contributions and theoretical for the institution. Methodology: We used the scientific methods of action research, involving quantitative and qualitative methods, documentary research and bibliographic research. It was observed that all journals adopt the standard SEER / OJS (Electronic Publishing Service), use the Digital Object Identifier (DOI) and are integrated with the portal's institutional link. However, only 45% of the journals are empowered with the LOCKSS manifesto for digital preservation through the Carian Network. Results: It was also verified that the UFPA periodicals have well-defined editorial policies aimed at quality and is still seeking to institutionalize a conservation policy digital. Conclusions: Thus, we conclude that digital preservation presents itself as a a decisive and growing factor for the guarantee of past production and the the maintenance of this knowledge with the objective of making them available for the present and future generations.